Science, technology & innovation policy review (STIP) : review of Mauritania - Lim, Michael (UN New YorkUS, 2010)
Aims to provide an independent and constructive assessment of STI capabilities and policies and the NSI in Mauritania; evaluates the priority that should be placed on remedying them; and suggests some concrete measures that could contribute to this in light of the country's specific circumstances.